NANOENKAPSULASI ASAM STEARAT DENGAN MODIFIKASI GRAFENA mG/SA WALL-CORE SEBAGAI KOMPOSIT PERUBAHAN FASA - Saharman Gea; Vivi Purwandari (UIN AR-RANIRY, 2020)
The fabrication of phase-changed composite (PCC) utilized to store thermal energy through encapsulation has been performed by utilizing the stearate acid (SA) and modified graphene (mG) with sentrimoinum bromide (CTAB). The composite was fabricated via latex method, while the liquid SA was able to be encapsulated and stabilized due to the presence of mG. The active phase of SA altered to be a thermal storing site obtained from latent heat, while the mG wall has protective features which can prevent the leakage of SA core during the transition phase. The active phase itself increased the thermal conductivity from 4.93 W/mK to 7.65 W/mK with maximum storing energy for 84.8%. The stable form of mG was measured extremely low for 2 phr with an average particle size of 13.68 nm. Thus, mG wall has excellent thermal stability and effective protection in shielding the SA core which improves the thermal properties of the composite.